Synthesis and photophysical properties of 1, 7-aroyl BODIPYs: an experimental and theoretical study. (30th September 2022) - Efimov, Ilya V.; Miftyakhova, Almira R.; Matveeva, Maria D.; Zhilyaev, Dmitry I.; Czulkin, Paweł.; Janasik, Patryk; Talarico, Giovanni; Voskressensky, Leonid G.
Abstract : The introduction of electron donating groups or electron withdrawing groups into the phenyl ring at the meso position of 1, 7-aroyl BODIPY significantly influences the fluorescence quantum yield. Abstract : A series of new boron-dipyrromethenes bearing an aroyl functionality have been efficiently synthesized through the reaction of 2, 4-disubstituted pyrroles with aromatic aldehydes followed by oxidation with DDQ and reaction with BF3 OEt2 . The investigation of the photophysical properties of the prepared compounds revealed that they have a maximum of absorption 565 ± 5 nm and a maximum of emission at 620 ± 10 nm in DCM with quantum yields from 12% up to 96%. It was discovered the introduction of electron-donating substituents into the phenyl ring at the meso position of BODIPY significantly reduces the fluorescence quantum yield. Density functional theory (DFT)/time-dependent-DFT calculations (TD-DFT) reproduced the main features of these new compounds.